2021
DOI: 10.3390/f12050590
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Material Resistance of Wood—Part 3: Relative Resistance in above- and in-Ground Situations—Results of a Global Survey

Abstract: Durability-based designs with timber require reliable information about the wood properties and how they affect its performance under variable exposure conditions. This study aimed at utilizing a material resistance model (Part 2 of this publication) based on a dose–response approach for predicting the relative decay rates in above-ground situations. Laboratory and field test data were, for the first time, surveyed globally and used to determine material-specific resistance dose values, which were correlated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In the general service-life design framework, the resulting exposure dose is then combined with a material-inherent resistance dose to account for the protective properties (natural, modified, or treated) and moisture dynamics (wetting ability) of the specific material [20,21]. For terrestrial environments (use-class 4), the wood moisture content is influenced by the soil and can often be assumed to remain permanently damp [35,36].…”
Section: In-ground Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general service-life design framework, the resulting exposure dose is then combined with a material-inherent resistance dose to account for the protective properties (natural, modified, or treated) and moisture dynamics (wetting ability) of the specific material [20,21]. For terrestrial environments (use-class 4), the wood moisture content is influenced by the soil and can often be assumed to remain permanently damp [35,36].…”
Section: In-ground Contactmentioning
confidence: 99%
“…The exposure dose can then be described as a function of wood temperature, which may be determined by modelling the soil temperature. Using the same assumption, the material-inherent resistance dose is determined independent of moisture dynamics and focused on soil-contact decay tests either under laboratory or field conditions [36].…”
Section: In-ground Contactmentioning
confidence: 99%
“…In this study, the aims were to: 1. compare the material resistance and moisture performance of the three European reference wood species (Norway spruce, European beech and Scots pine sapwood) with conversion factors as the primary output (this paper), 2. collecting data from durability tests for validating and optimizing the 'Meyer-Veltrup model' for material-resistance [7] and Part 2 of this publication [19], and 3. surveying wood durability test data, utilize them for implementation in a material resistance model, and generate a database for service life prediction of wood products in above and in-ground situations, Part 3 of this publication [20].…”
Section: Introductionmentioning
confidence: 99%
“…They represent a wide range of aspects related to performance modeling of wood and wood products and give timely examples of research activities that can be observed around the globe. Several authors reported on engineering approaches to predict and plan the service lives of buildings and structures made of wood [1][2][3], models focusing on material properties such as material resistance against decay agents [3][4][5][6][7], basic wood properties and their distribution in trees [8], and new methods of monitoring performance-related parameters [9]. The link between exposureinduced dosage and material-inherent resistance were established for a variety of use conditions, such as soil contact and different above-ground scenarios [2][3][4][5]7,10,11].…”
mentioning
confidence: 99%
“…Several authors reported on engineering approaches to predict and plan the service lives of buildings and structures made of wood [1][2][3], models focusing on material properties such as material resistance against decay agents [3][4][5][6][7], basic wood properties and their distribution in trees [8], and new methods of monitoring performance-related parameters [9]. The link between exposureinduced dosage and material-inherent resistance were established for a variety of use conditions, such as soil contact and different above-ground scenarios [2][3][4][5]7,10,11]. Finally, even a model describing the performance of media presenting wood-based products is presented [12].…”
mentioning
confidence: 99%